1996
DOI: 10.1016/0009-2509(96)00080-2
|View full text |Cite
|
Sign up to set email alerts
|

Flammability limits in flowing ethene-air-nitrogen mixtures: An experimental study

Abstract: A large pilot plant was constructed to study the upper flammability limit of ethene-air-nitrogen mixtures under conditions of flow. The gas mixtures flowed through an explosion tube with a length of 3.0 m and a diameter of 21 ram. An electrically heated wire was used as ignition source. Experiments were performed at pressures of 5 and 10 bar, with gas temperatures between 25 and 300 °C and with the wire fixed horizontally and vertically. Three different phenomena are observed: negligible reaction, local reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…1.5 MPa. Bolk et al 1996 did similar tests in a smaller 21-mm tube and found a flame temperature of around 1,500 K at a pressure of 0.5 MPa.…”
Section: Experiments At Different Temperaturesmentioning
confidence: 84%
See 3 more Smart Citations
“…1.5 MPa. Bolk et al 1996 did similar tests in a smaller 21-mm tube and found a flame temperature of around 1,500 K at a pressure of 0.5 MPa.…”
Section: Experiments At Different Temperaturesmentioning
confidence: 84%
“…Some results have been pre-Ž . sented by Bolk et al 1996 , and others will be presented in a later study. The best fit for ␤ equals 1.53=10 y3 kgrm 3 , and this finally leads to Eq.…”
Section: žmentioning
confidence: 99%
See 2 more Smart Citations
“…wire. Westerterp 1993 andBolk et al 1996 showed that the upper explosion limit strongly depends on the flow rate of the gas; an increase in flow rate makes the explosion region smaller.…”
mentioning
confidence: 99%